Reflexive witnessing: Boyle, the Royal Society and scientific style. (30th January 2019) - Hogarth, Alan James; Witmore, Michael
Abstract : This article uses quantitative methods to analyse the language of Royal Society prose. Historians of science such as Barbara Shapiro have argued that specific linguistic features are detectable in the Royal Society's experimental reports, including first-person reporting and expressions of modesty. Moreover, Steven Shapin and Simon Schaffer's influential study of Royal Society writing suggests that such linguistic strategies are designed to establish trust in the reporter and enable readers to become 'virtual witnesses' to experimental activities. While previous scholarship has persuasively identified distinct modes of rhetorical appeal in Royal Society texts, our corpus-based linguistic approach offers a more fine-grained description of the rhetoric of modesty and witnessing identified by other scholars. Our analysis further suggests that Royal Society writers had a self-reflexive and temporally complex relationship with the process of inquiry that is not fully captured by these qualitative studies; we call this linguistic structure 'reflexive witnessing'. Having defined that structure linguistically and surveyed it across a broader range of early modern texts, we demonstrate that 'reflexive witnessing' was not exclusive to the community of the Royal Society.